Effect of E-Satisfaction on Repurchase Intention in Shopee User Students - Saut Maruli Tua Pandiangan; Ira Ningrum Resmawa; Owen De Pinto Simanjuntak; Pretty Naomi Sitompul; Riny Jefri (Budapest International Research and Critics University, 2021)
People's shopping style is now traditional again, which usually comes to the market to buy an item, but now people can shop online just by pressing their smartphone screen while sitting relaxed at home. This study aims to determine and analyze the effect of the e-satisfaction variable on the repurchase intention variable at shopee at the students of Politeknik IT&B Medan. This type of research is quantitative research with causality research design. The population in this study were all Politeknik IT&B Medan, majoring in Business Administration Management, semester 2 and 4, who had shopped at least twice using the Shopee e-commerce application. The sample in this study were 47 people. The data analysis method used was simple linear regression with partial test (t), and the coefficient of determination (R2). The results showed that the e-satisfaction variable had a positive and significant effect on the repurchase intention variable. The e-satisfaction variable can explain the repurchase intention variable by 64.6% and the remaining 35.4% is explained by other variables not examined in this study.